2003
DOI: 10.1007/s11746-003-0838-2
|View full text |Cite
|
Sign up to set email alerts
|

Phase behavior of a binary lipid shortening system: From molecules to rheology

Abstract: The phase behavior of fully hydrogenated canola oil in soybean oil was investigated using iso-solid lines from temperature-controlled pulse-NMR along with DSC data, with the rate of cooling of crystallized samples kept constant. The molecular diversity within the fat system was investigated using HPLC and GC. The microstructure of the fats was determined using a temperature-controlled polarized light microscope, and the polymorphism of the solidified fat structures was determined via a temperature-controlled X… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
32
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 8 publications
7
32
0
Order By: Relevance
“…Means among duplicate sample injections blends, with coefficients of determination (R 2 ) higher than 0.90, as in Figure 3. A similar relation among these parameters and hardfats concentration is observed by Humphrey et al 42 and by Humphrey and Narine 43 in studying blends containing various liquid and fully hydrogenated oils.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…Means among duplicate sample injections blends, with coefficients of determination (R 2 ) higher than 0.90, as in Figure 3. A similar relation among these parameters and hardfats concentration is observed by Humphrey et al 42 and by Humphrey and Narine 43 in studying blends containing various liquid and fully hydrogenated oils.…”
Section: Resultssupporting
confidence: 83%
“…DeMan et al 66 report the β′ polymorph in fully hydrogenated canola oil, which characteristically tends to β stabilize. Humphrey et al 42 , evaluating polymorphic behavior in soybean oil/fully hydrogenated canola oil blends, found that the polymorphic forms varied with the concentration of fully hydrogenated canola oil in the samples. According to Metin and Hartel 30 and Kloek et al 52 , the persistence of β′ crystals in cases where stabilization is preferentially β-type probably results from the formation of mixed crystals, which may be favored by the triacylglycerol composition of the blend and by the tempering protocol used, particularly when a high degree of super-cooling occurs.…”
Section: Resultsmentioning
confidence: 99%
“…Binary mixtures of MMS/MSM were prepared in molar ratios of 0.0, 0.1, 0.2, 0.4, 0.6, 0.8 and 1.0 as a function of MSM composition. Samples were prepared as detailed elsewhere (Humphrey et al, 2003).…”
Section: Sample Preparationmentioning
confidence: 99%
“…The original blends showed a prominent peak in the crystallization curve, which characterizes the trisaturated fraction of palm stearin and palm kernel oil, containing high melting point triacylglycerols. These results confirmed those of Humphrey, Moquin, and Narine (2003), which showed that an increase in the number of molecules with simultaneous crystallization leads to a larger energy release by the system. Enzymatic interesterification resulted in the appearance of other peaks in the crystallization curves, which is characteristic of the increase in the middle-melting-point TAG (SSO, SOO, and POS) content due to the exchange of acyl groups between TAGs.…”
Section: Thermal Propertiessupporting
confidence: 86%